Kastracja przestępców seksualnych w Trzeciej Rzeszy w świetle śląskich dokumentów prowincjonalnych - Kruszewski, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The author examines one of the notorious elements of Nazi criminal law, i.e. castration of sexual offenders introduced in 1933. The issue is analysed in the context of documents of the Provizialverband Niederschlesien, preserved in the State Archives in Wrocław, which include fi les entitled Kastration der Sexualverbrecher. The paper combines an analysis — carried out from the point of view of the legal dogma — of Third Reich laws amended Articles 42k and 226a of the StGB with the literature on the subject. However, the author’s main objective is to discuss the surviving archive documents from Silesia.
Keywords: Trzecia Rzesza; prawo karne; kastracja; przestępstwa seksualne; kara; totalitaryzm; nazizm